Preparation method of high-strength ultrathin light Al / Mg-Li / Al composite foil
Through stacking and cold rolling technology and room temperature rolling process, high-strength ultra-thin and lightweight Al/Mg-Li/Al composite foils were prepared, which solved the problems of high preparation costs and lack of large-scale production technology in the existing technology, and achieved high efficiency , low-cost foil preparation.
Patent Information
- Application Number
- CN202510058830.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively prepare high-strength ultra-thin and lightweight Al/Mg-Li/Al composite foils, and the preparation cost of magnesium alloy foils is high and lacks the technology for large-scale production.
The aluminum layer is coated on the surface of the magnesium lithium alloy by stacking technology. Through multiple cold rolling processes at room temperature, the foil thickness is gradually reduced, combined with inert gas protection and finishing treatment, high-strength ultra-thin and lightweight Al/Mg is prepared. -Li/Al composite foil.
The high-strength, ultra-thin and lightweight properties of the foil are achieved, which reduces the preparation cost, simplifies the process flow, is easy to produce on a large scale, and improves the dimensional accuracy and surface finish of the foil.
Smart Images

Figure CN119456676A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of alloy materials, and in particular relates to a method for preparing a high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil. Background Art
[0002] As the lightest metal structural material, magnesium-lithium alloy has high specific strength, high specific stiffness and excellent damping properties, and has broad application prospects in aerospace, electronic products, medical equipment, automobiles and other fields. However, the strength, elastic modulus and corrosion resistance of magnesium-lithium alloy seriously restrict its industrial application. Aluminum and aluminum alloys also have advantages such as low density, strong corrosion resistance, good impact absorption and processing formability, and are widely used in the food industry, chemical industry, aerospace and automobile industry. Aluminum is often added in the alloying treatment of magnesium-lithium alloy, which can improve its strength and corrosion resistance; plastic deformation can also effectively improve the microstructure and mechanical properties of magnesium alloy materials. Therefore, by using the rolling technology to coat a layer of aluminum with good corrosion resistance on the surface of magnesium-lithium alloy to form a "sandwich" layered material, it can protect magnesium-lithium alloy from corrosion while improving its strength, thereby preparing an excellent new Al / Mg-Li / Al composite material. On the other hand, for traditional magnesium alloys, due to their hexagonal close-packed structure (HCP) characteristics, it is difficult to perform plastic deformation at room temperature, let alone form magnesium alloy foil at room temperature. The addition of lithium can significantly improve the plasticity of magnesium alloys, especially when the lithium content exceeds 10.3 wt.%, the crystal structure of the magnesium alloy will be completely transformed into a body-centered cubic structure (BCC), which greatly improves its room temperature ductility. Since both magnesium-lithium alloys with high lithium content and pure aluminum materials have high plastic deformation capabilities and strong coordinated deformation capabilities, it is possible to stack the two and use room temperature rolling technology to prepare foils. At the same time, due to the introduction of large plastic deformation (accumulated stacking) and Mg / Al composite heterogeneous structure, the mechanical properties of Al / Mg-Li / Al composite foils will also be improved.
[0003] Magnesium alloy foil refers to thin plate and strip. The existing preparation process is difficult to achieve large-scale production, and the cost remains high. In recent years, although many researchers have developed a series of foil preparation technologies for magnesium-lithium alloys, such as CN200910307937.2, which disclosed a rolling method for magnesium or magnesium alloy foil; CN201210100705.1, which disclosed a magnesium alloy sheet coil / foil rolling method and its roller system; and patent CN102649124A, which disclosed a rolling method for magnesium or magnesium alloy foil by coating aluminum plates into a stacked rolling package, cutting off the coating edge after rolling, and separating the foil, these patents all require hot rolling or annealing to ensure the rolling quality, and the processing procedures are relatively complicated and the cost is high. Moreover, they are only single magnesium or magnesium alloy foils, and there is no report or disclosure of the preparation technology of related Al / Mg-Li / Al laminated composite foils. Summary of the invention
[0004] In order to solve the problem that the preparation cost of magnesium alloy foil is high and the preparation of Al / Mg-Li / Al laminated composite foil is still blank in the prior art, the present invention mainly provides a high-strength ultra-thin and lightweight Al / Mg-Li / Al composite foil and the preparation technology and processing scheme of the foil: A method for preparing a high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil comprises the following steps: a. Cutting the magnesium-lithium alloy and aluminum into blocks to obtain magnesium-lithium alloy plates and aluminum plates; b. Place a clean magnesium-lithium alloy plate in the middle, place clean aluminum plates on the upper and lower surfaces of the magnesium-lithium alloy plate, and stack them, and fix and tie them with aluminum wire to obtain an Al / Mg-Li / Al stacked plate; c. In an inert gas atmosphere, the Al / Mg-Li / Al stacked sheet is preheated at 300-450°C for 5-10 min, and then quickly rolled at a reduction of 40-60% to obtain an Al / Mg-Li / Al composite sheet. d. At room temperature, the Al / Mg-Li / Al composite sheet was subjected to multiple cold rolling with a small deformation amount of 2-30% to a thickness of 0.5-1 mm; then, it was subjected to multiple cold rolling with a large deformation amount of 30-50% to a target thickness.
[0005] Furthermore, the cold-rolled Al / Mg-Li / Al composite foil is finished to solve the problems of wavy edges, coil cracks and center bumps, and the thickness tolerance is less than ±0.005.
[0006] Furthermore, the magnesium-lithium alloy plate in step a has the same length and width as the aluminum plate.
[0007] Furthermore, the small deformation multi-pass cold rolling in step d means that the reduction before the plate thickness drops to 1-3 mm is 2-10% to avoid cracking of the plate due to excessive reduction, and the reduction in all subsequent passes is 10-30% until the plate thickness is rolled to not less than 0.5 mm.
[0008] Furthermore, the large deformation multi-pass cold rolling in step d means that the reduction in the first three passes is 30-40%, and the reduction in the subsequent passes is 40-50%, until the thickness of the Al / Mg-Li / Al foil is rolled to the target thickness.
[0009] Furthermore, in step d, the foil is cold rolled in multiple passes with a large deformation amount until the thickness is 0.1-0.05 mm, and then the cold rolling is repeated until the foil thickness reaches the target thickness.
[0010] Furthermore, the rolling force of the repeated cold rolling is 0.05-0.01 ton / mm 2 .
[0011] Furthermore, before stacking the magnesium-lithium alloy plate and the aluminum plate, the magnesium-lithium alloy plate and the aluminum plate are surface treated, including the following steps: cleaning the magnesium-lithium alloy plate with dilute nitric acid, cleaning the aluminum plate with a mixed solution of dilute hydrochloric acid and hydrofluoric acid, then grinding the plate surface to remove the oxide film, then washing with acetone to remove grease on the plate surface, rinsing with ethanol to remove surface impurities, then blowing dry, and finally grinding the alloy surface to expose fresh metal to obtain clean magnesium-lithium alloy plate and aluminum plate.
[0012] A high-strength, ultra-thin, lightweight Al / Mg-Li / Al composite foil prepared by the above method has a middle layer of magnesium-lithium alloy and a surface layer of aluminum.
[0013] Furthermore, the thickness is 0.02~0.1mm; wherein the thickness ratio of the aluminum in the surface layer to the magnesium-lithium alloy in the middle layer is 0.01~1:1.
[0014] Furthermore, the magnesium-lithium alloy has a body-centered cubic structure; the magnesium-lithium alloy includes 10.3-20wt.% lithium, 0.01-20wt.% zinc, the total amount of unavoidable impurities is less than 0.03%, and the balance is magnesium. The aluminum plate includes 99.7-99.8wt.% aluminum, and the total amount of unavoidable impurities is less than 0.03%.
[0015] By adopting the above scheme, the method of the present invention has the following advantages: The present invention firstly performs rolling with a reduction of 40-60% to obtain an Al / Mg-Li / Al composite plate, and then performs multiple cold rolling at room temperature, so that the Al / Mg-Li / Al composite foil is prepared with fewer steps, the rolling process is simple, the cost is low, and large-scale batch production can be easily realized.
[0016] The method of the invention realizes a large cumulative cold rolling deformation, improves the dimensional accuracy of the foil, and the thickness deviation can reach ±0.002mm.
[0017] In the processing of the present invention, only the initial composite plate is processed at 300-450°C, and the rest are processed at room temperature, which solves the problem that the annealing process in the magnesium alloy cold rolling process in the prior art easily causes the foil surface to oxidize, and the obtained foil has a high surface finish.
[0018] The present invention first performs heat preservation treatment in an atmosphere of protective gas, and quickly rolls the plate to be laminated into a composite plate. This process greatly reduces surface oxidation, and the interface of the composite plate is easier to combine, providing a good basis for rolling the composite plate into foil.
[0019] The present invention can obtain a finely rolled Al / Mg-Li / Al composite foil with good flatness and less burrs after multiple passes of room temperature cold rolling, with low energy consumption and high yield rate. In addition, the present invention can use a small-tonnage multi-roll mill or a single-roll mill to prepare ultra-thin foil, and the preparation of the foil has low requirements on equipment.
[0020] The foil of the present invention combines the advantages of magnesium-lithium alloy and aluminum alloy, and its strength is greatly improved. The tensile strength of the 0.02 mm foil reaches 375 MPa, the thickness deviation is ±0.002 mm, the flatness is good, and the burrs are few. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a photograph of the initial Al / Mg-Li / Al composite foil.
[0022] Figure 2 is a photo of 0.1 mm thick Al / Mg-Li / Al composite foil.
[0023] Figure 3 is a photo of 0.05 mm thick Al / Mg-Li / Al composite foil.
[0024] Figure 4 This is a photo of a 0.02 mm thick Al / Mg-Li / Al composite sheet.
[0025] Figure 5 This is a thickness photo of 0.02mm thick Al / Mg-Li / Al composite foil.
[0026] Figure 6 This is a microstructure photo of 0.02mm thick Al / Mg-Li / Al composite foil.
[0027] Figure 7It is the room temperature engineering stress-strain curve of Al / Mg-Li / Al composite plate / foil with different thickness specifications. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1: (1) A magnesium-lithium alloy and a 1060 pure aluminum plate with an aluminum purity of 99.7-99.8 wt.%, wherein the magnesium-lithium alloy comprises, by mass percentage, 11% Li and 6% Zn, and the total amount of inevitable impurities of Fe, Cu, Ni, Mn, and Si is less than 0.03%, and the balance is Mg; (2) Treatment of magnesium-lithium alloy and pure aluminum raw materials to be rolled: (a) Cutting the magnesium-lithium alloy ingot and 1060 pure aluminum sheet to be accumulated and rolled into blocks with the same length and width and different thickness (the thickness of magnesium-lithium alloy is greater than that of pure aluminum); (b) Performing surface treatment, cleaning the magnesium-lithium alloy sheet with dilute nitric acid, cleaning the 1060 pure aluminum sheet with a mixed solution of dilute hydrochloric acid and hydrofluoric acid, then grinding the sheet surface with sandpaper to remove the oxide film, then washing with acetone to remove the grease on the sheet surface, rinsing with anhydrous ethanol to remove surface impurities, then drying with a hair dryer, and finally grinding the alloy surface with a steel wire brush to expose fresh metal; (c) Stacking the magnesium-lithium alloy sheet and the aluminum alloy sheet obtained in step b in the form of Al / Mg-Li / Al, and fixing and bundling them with fine aluminum wire (diameter 0.1 mm); (3) Preparation of Al / Mg-Li / Al composite sheet: The Al / Mg-Li / Al stacked plate obtained in the above steps was preheated at 400°C for 10 min under argon protection, and then quickly rolled at a 50% reduction to obtain an initial Al / Mg-Li / Al composite plate; Figure 1 This is the initial Al / Mg-Li / Al composite sheet obtained in step (3). As can be seen from the figure, the magnesium-lithium alloy and the upper and lower pure aluminum sheets are tightly bonded.
[0030] (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, the initial Al / Mg-Li / Al composite sheet was subjected to multiple cold rolling with a reduction of 2-30% using a small-tonnage single-roll / multi-roll mill. The reduction before the sheet thickness dropped to 3 mm was 2-10% to avoid cracking of the sheet due to excessive reduction, and the reduction for all subsequent passes was 10-30% until the sheet thickness was reduced to 0.5 mm. Subsequently, the 0.5 mm thick composite sheet was subjected to multiple cold rolling with a reduction of 30%-50%, wherein the reduction for the first three passes was 30-40%, and the reduction for all subsequent passes was 40-50%, until the thickness of the composite sheet dropped to 0.1 mm.
[0031] Figure 2 The Al / Mg-Li / Al composite foil with a thickness of 0.1 mm is obtained. As can be seen from the figure, the surface of the obtained foil is smooth, there is no separation between the aluminum layer and the alloy layer, and the layers are tightly bonded to form a complete whole.
[0032] Embodiment 2: The difference from Embodiment 1 is that: (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, a small-tonnage single-roll / multi-roll mill is used to cold-roll the 5 mm thick initial billet in multiple passes with a reduction of 2-30%. The reduction before the plate thickness is reduced to 3 mm is 2-10% to avoid cracking of the plate due to excessive reduction. The reduction of all subsequent passes is 10-30% until the plate thickness is reduced to 0.5 mm. Subsequently, the 0.5 mm thick composite plate is cold-rolled in multiple passes with a reduction of 30%-50%, of which the reduction of the first three passes is 30-40%, and the reduction of all subsequent passes is 40-50%, until the thickness of the composite plate is reduced to 0.05 mm.
[0033] Figure 3 The obtained Al / Mg-Li / Al composite foil has a thickness of 0.05 mm. As can be seen from the figure, the surface of the obtained foil is smooth, there is no separation between the aluminum layer and the alloy layer, the interface between the layers is well bonded, and no obvious defects are observed.
[0034] Embodiment 3: The difference from Embodiment 1 is that: (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, a small-tonnage single-roll / multi-roll mill is used to perform multiple cold rolling with a reduction of 2-30% on the 5 mm thick initial billet. Among them, the reduction before the plate thickness is reduced to 3 mm is 2-10% to avoid cracking of the plate due to excessive reduction. The reduction of all subsequent passes is 10-30% until the plate thickness is reduced to 0.5 mm. Subsequently, the 0.5 mm thick composite plate is subjected to multiple cold rolling with a reduction of 30%-50%, among which the reduction of the first three passes is 30-40%, and the reduction of all subsequent passes is 40-50%, until the thickness of the composite plate is reduced to 0.05 mm; (5) At room temperature, increase the rolling force between the two rolls of a small-tonnage single-roller / multi-roller mill to 0.01-0.05 tons / mm 2 , repeatedly cold rolling the Al / Mg-Li / Al composite foil until the foil is rolled to a thickness of 0.02 mm; (6) The Al / Mg-Li / Al composite foil after fine rolling is finished to completely solve the problems of wavy edges, coil cracks and center bumps, and the thickness tolerance is less than ±0.002.
[0035] Figure 4 and Figure 5 The Al / Mg-Li / Al composite foil with a thickness of 0.02 mm is obtained. As can be seen from the figure, the surface of the obtained foil is flat and smooth without obvious defects.
[0036] Figure 6 From the microstructure photos, it can be seen that the outermost layer of aluminum wraps the internal magnesium-lithium alloy material very well, the Al / Mg interface is well bonded, and there are no obvious defects.
[0037] Comparative Example 1: The difference from Example 1 is: (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, the initial Al / Mg-Li / Al composite sheet was cold rolled in multiple passes with a reduction of 2-30% using a small-tonnage single-roll / multi-roll mill. The reduction before the sheet thickness was reduced to 3 mm was 2-10% to avoid excessive reduction causing sheet cracking, and the reduction in all subsequent passes was 10-30% until the sheet thickness was reduced to 2 mm.
[0038] Comparative Example 2: The difference from Example 1 is: (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, the initial Al / Mg-Li / Al composite sheet was cold rolled in multiple passes with a reduction of 2-30% using a small-tonnage single-roll / multi-roll mill. The reduction was 2-10% before the sheet thickness was reduced to 3 mm to avoid cracking of the sheet due to excessive reduction, and the reduction in all subsequent passes was 10-30% until the sheet thickness was reduced to 1 mm.
[0039] Comparative Example 3: The difference from Example 1 is: (4) Cold rolling with small deformation and then cold rolling with large deformation: At room temperature, the initial Al / Mg-Li / Al composite sheet was cold rolled in multiple passes with a reduction of 2-30% using a small-tonnage single-roll / multi-roll mill. The reduction was 2-10% before the sheet thickness was reduced to 3 mm to avoid cracking of the sheet due to excessive reduction, and the reduction in all subsequent passes was 10-30% until the sheet thickness was reduced to 0.5 mm.
[0040] Example sample test: The tensile strength of each embodiment and comparative example was tested, and the engineering stress-strain curve was drawn. The results are as follows: Figure 7 As shown in the figure, it can be seen that the tensile strength of the Al / Mg-Li / Al composite plate / foil increases with the decrease of thickness, among which the tensile strength of the 0.02 mm specification foil reaches 375 MPa.
[0041] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil, characterized in that: The following steps are involved: a. Cutting the magnesium-lithium alloy and aluminum into blocks to obtain magnesium-lithium alloy plates and aluminum plates; b. Place a clean magnesium-lithium alloy plate in the middle, place clean aluminum plates on the upper and lower surfaces of the magnesium-lithium alloy plate, and stack them, and fix and tie them with aluminum wire to obtain an Al / Mg-Li / Al stacked plate; c. In an inert gas atmosphere, preheat the Al / Mg-Li / Al stacked sheet at 300-450°C for 5-10 min, take it out and quickly roll it at a reduction of 40-60% to obtain an Al / Mg-Li / Al composite sheet; d. At room temperature, the Al / Mg-Li / Al composite sheet is subjected to multiple cold rolling with a small deformation amount of 2-30% reduction to a thickness of 0.5-1 mm; then, the Al / Mg-Li / Al composite sheet is subjected to multiple cold rolling with a large deformation amount of 30-50% reduction to a target thickness.
2. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 1, characterized in that: The magnesium-lithium alloy plate in step a has the same length and width as the aluminum plate.
3. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 1, characterized in that: The small deformation multi-pass cold rolling in step d means that the reduction before the plate thickness is reduced to 1-3 mm is 2-10%, and the reduction in all subsequent passes is 10-30% until the plate thickness is rolled to not less than 0.5 mm.
4. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 1, characterized in that: The large deformation multi-pass cold rolling in step d means that the reduction in the first three passes is 30-40%, and the reduction in the subsequent passes is 40-50%, until the thickness of the Al / Mg-Li / Al foil is rolled to the target thickness.
5. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 1, characterized in that: Step d: cold rolling is performed in multiple passes with a large deformation amount until the thickness is 0.1-0.05 mm, and then cold rolling is continued repeatedly until the foil thickness reaches the target thickness.
6. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 5, characterized in that: The rolling force for repeated cold rolling is 0.05-0.01 ton / mm 2 .
7. The method for preparing the high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 1, characterized in that: Before stacking the magnesium-lithium alloy plate and the aluminum plate, the magnesium-lithium alloy plate and the aluminum plate are surface treated, including the following steps: cleaning the magnesium-lithium alloy plate with dilute nitric acid, cleaning the aluminum plate with a mixed solution of dilute hydrochloric acid and hydrofluoric acid, then grinding the plate surface to remove the oxide film, then cleaning with acetone to remove grease on the plate surface, rinsing with ethanol to remove surface impurities, then blowing dry, and finally grinding the alloy surface to expose fresh metal to obtain clean magnesium-lithium alloy plate and aluminum plate.
8. A high-strength, ultra-thin, lightweight Al / Mg-Li / Al composite foil prepared by the method according to any one of claims 1 to 7, characterized in that: The middle layer is magnesium-lithium alloy and the surface layer is aluminum.
9. The high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 8, characterized in that: The thickness is 0.02~0.5mm; the thickness ratio of the aluminum in the surface layer to the magnesium-lithium alloy in the middle layer is 0.01~1:
1.
10. The high-strength ultra-thin lightweight Al / Mg-Li / Al composite foil according to claim 8, characterized in that: The magnesium-lithium alloy has a body-centered cubic structure; the magnesium-lithium alloy includes 10.3-20wt.% lithium, 0.01-20wt.% zinc, and the balance is magnesium.
Citation Information
Patent Citations
Rolling manufacture method for magnesium or magnesium alloy foil
CN101658859B
Magnesium alloy sheet material coiled (foil) material rolling method and roll system thereof
CN102615101B
Rolling method of magnesium or magnesium alloy foils
CN102649124A
Method for preparing aluminum-magnesium ultrafine crystal composite plate with multilayer structure
CN101530860A
Magnesium lithium-aluminum composite material and preparation method thereof
CN116078817A